Utility of tricalcium phosphate and osteogenic matrix cell sheet constructs for bone defect reconstruction - Ueha, Tomoyuki (World J Stem Cells, 2015)
AIM: To determine the effects of transplanting osteogenic matrix cell sheets and beta-tricalcium phosphate (TCP) constructs on bone formation in bone defects. METHODS: Osteogenic matrix cell sheets were prepared from bone marrow stromal cells (BMSCs), and a porous TCP ceramic was used as a scaffold. Three experimental groups were prepared, comprised of TCP scaffolds (1) seeded with BMSCs; (2) wrapped with osteogenic matrix cell sheets; or (3) both. Constructs were implanted into a femoral defect model in rats and bone growth was evaluated by radiography, histology, biochemistry, and mechanical testing after 8 wk. RESULTS: In bone defects, constructs implanted with cell sheets showed callus formation with segmental or continuous bone formation at 8 wk, in contrast to TCP seeded with BMSCs, which resulted in bone non-union. Wrapping TCP constructs with osteogenic matrix cell sheets increased their osteogenic potential and resulting bone formation, compared with conventional bone tissue engineering TCP scaffolds seeded with BMSCs. The compressive stiffness (mean ± SD) values were 225.0 ± 95.7, 30.0 ± 11.5, and 26.3 ± 10.6 MPa for BMSC/TCP/Sheet constructs with continuous bone formation, BMSC/TCP/Sheet constructs with segmental bone formation, and BMSC/TCP constructs, respectively. The compressive stiffness of BMSC/TCP/Sheet constructs with continuous bone formation was significantly higher than those with segmental bone formation and BMSC/TCP constructs. CONCLUSION: This technique is an improvement over current methods, such as TCP substitution, and is useful for hard tissue reconstruction and inducing earlier bone union in defects.